UV-initiated synthesis of superporous cryogel loaded with palladium nanoparticles for effective catalytic degradation of Eosin Y - Abdul Haleem; Jaweria Ambreen; Syeda Huma H. Zaidi; Mohamed Soliman; Nadeem Kizilbash; Daliyah Alruwaili; Jamith Basha; Syafiqah Saidin (Desalination and Water Treatment)
The fabrication of macroporous materials exhibiting catalytic properties to degrade detrimental toxicants from water has gained significant interest. Herein, acrylamide-based pure cryogels were synthesized by UV-initiated free radical cryopolymerization method and were further incorporated with palladium nanoparticles employing the in situ chemical reduction method. The verification of the functional groups for the cryogels was done by using Fourier-transformed infrared spectroscopy. The formation of cryogels was confirmed by X-ray diffraction, energy-dispersive X-ray and transmission electron microscopic methods, respectively. The macroporous morphological analysis of cryogels was done by scanning electron microscopy. Moreover, Thermo-gravimetric analysis showed that palladium incorporated cryogels exhibit more thermal stability as compared to pure cryogels. The palladium incorporated cryogel was implemented for degrading an organic dye, Eosin Y. The catalysis efficiency of Pd-incorporated cryogels was also compared to a conventional Pd-embedded hybrid hydrogel. The impact of cross-linker content, temperature, and catalyst amount on degradation rate was studied by UV–visible spectroscopy. The degradation time for Eosin Y dye using 0.5 g of Pd-nanoparticles embedded cryogel with 3 % crosslinker content was 10 min at 25 ºC. By considering their feasible UV-initiated synthesis route and adsorption enactment, the fabricated cryogel could be applied as a suitable prototype for water clean-up solutions.